Theoretical Calculations for the Acidity of Cyanopolyynes HC2n+1N (n = 0–5) in Gas and Aqueous Phases Using Ab initio Methods - Abdallah, Hassan H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
Cyanopolyynes have been found in the interstellar medium, cold dust cloud Taurus Molecular Cloud-1, and the Titan’s atmosphere. Theoretical calculations are carried out to predict gas and aqueous phase acidities of a series of cyanopolyynes acids. Two levels of theory were used in this study, with the combination of density functional theory, and Møller–Plesset perturbation (MP2) theory, MP2 methods with two types of basis set, namely, Pople’s 6–311++g (d, p) basis set and Dunning’s aug-cc-pVTZ basis set. The calculations of these molecules reveal that pKa values varying from 12.25 to 17.25 and indicate that the acidity of these molecules in aqueous phase increases whereas the acidity in gas phase decreases with an increasing chain length of these acids.